Unveiling the Influence of a High-Fat Meal on the Pharmacokinetics of Oral Globalagliatin, A Glucokinase Activator, in Healthy Chinese Volunteers - Maodi Xu; Yaqin Wang; Xiaohu Wang; Zhichen Pu; Ya Liu; Cuilian Jiang; Xiaokun Shen; Hua Sun; Haitang Xie (Adis, Springer Healthcare, 2023)
Abstract Introduction Glucokinase (GK) plays a pivotal role in maintaining glucose homeostasis; globalagliatin, a newly developed drug, is a GK activator (GKA). This study constitutes a randomized, open-label, two-cycle, two-crossover, single-dose, phase I clinical trial conducted at a single center with healthy Chinese volunteers, aiming to examine the influence of a high-fat meal on the pharmacokinetics (PK) of orally administered globalagliatin. Methods Twenty-four healthy volunteers were randomly divided into two groups, with a washout period of 16 days between the two cycles. The first cycle involved Group 1 volunteers who were orally administered globalagliatin 80 mg with 240 mL of water while fasting on Day 1. In contrast, Group 2 volunteers began oral administration of globalagliatin 80 mg with 240 mL of water, 30 min after consuming a high-fat meal (where high-fat content contributed to 54% of the total calories; the high-calorie meal amounted to 988.4 kcal). After the washout period, both groups of volunteers entered the second cycle of drug administration, with meals and medication being swapped on Day 17. Each volunteer collected blood samples at the following time points: 0 h (within 1 h before administration), and 0.5, 1, 2, 3, 4, 5, 6, 8, 12, 24, 48, 72, 96, 120, and 168 h after administration on both trial Day 1 and Day 17. The primary and secondary PK parameters were collected. The validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was used to determine the concentration of globalagliatin in collected plasma samples, and the results were analyzed using Phoenix WinNonlin software. Safety evaluation was conducted by detecting or observing various adverse events (AEs) and serious AEs (SAEs). Results All 24 healthy Chinese volunteers enrolled completed the study and underwent PK analysis. The maximum concentration (C max; ng/mL), area under the plasma concentration-time curve (AUC) from time zero to time of the last quantifiable concentration (AUC t ; h·ng/mL), and AUC from time zero extrapolated to infinity (AUC∞; h·ng/mL) of fasting administration were 22.35 ± 7.02, 725.74 ± 303.04, and 774.07 ± 343.89, respectively, while the C max, AUC t , and AUC∞ administered after a high-fat meal were 28.95 ± 12.60, 964.84 ± 333.99, and 1031.28 ± 392.80, respectively. The geometric mean ratios of C max, AUC t , and AUC∞ for high-fat meal/fasting administration of globalagliatin were 124.81%, 135.24%, and 135.42%, respectively, with 90% confidence intervals of 109.97-141.65, 124.24-147.20, and 124.42-147.39, respectively. Compared with the fasting state, healthy volunteers who consumed a high-fat meal showed a 24.8% increase in C max, a 35.2% increase in AUCt, and a 35.4% increase in AUC ∞ . The geometric mean of T max was 4.69 h under fasting conditions and 5.93 h in a high-fat state, with a median of 4.98 h. Among the 24 enrolled volunteers, 9 cases (37.5%) had 11 AEs, and 6 cases (25.0%) had 7 adverse drug reactions (ADRs) after medication, all of which were cured or improved without taking any treatment measures. There were no SAEs in this study, no volunteers withdrew from the study due to AEs or ADRs, and no hypoglycemic events occurred during the trial. Conclusion A high-fat meal increased the C max, AUCt, and AUC∞ of globalagliatin compared with fasting conditions in healthy Chinese adult volunteers. Meanwhile, globalagliatin showed favorable safety and tolerability under fasting or high-fat meal conditions.